Using Crossword Puzzle to Improve the Tenth Grade Students’ Vocabulary Mastery at SMK PGRI 3 TULUNGAGUNG in Academic Year 2015/ 2016 - Mitralia Mitralia; Piping Rahadiyanto; Ayu Riski Septiana (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2016)
From the research findings, it can be concluded thatcrossword puzzle has improved the students’ vocabulary mastery. The result ofthis study, from preliminary study showed that the students’vocabuary masterywas poor. The result of the cycle II indicated that students who passed thestudents who passed the test increased from 9 students or 45% in cycle I to 16student or 80% in cycle II. Therefore the researcher concludes that teachingvocabulary using crossword puzzle to the tenth grade students of SMK PGRI 3TULUNGAGUNG is effective to improve the students’vocabulary mastery, Andquestionnaires given to the students showed that the students enjoyed andincreased their vocabulary mastery by using crossword puzzle game.Key Term : Crossword Puzzle, Vocabulary Mastery